(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Mathematics has continued to increase its presence in the sciences and in the economic sectors, in general. Along with information technologies, huge volumes of data are processed that facilitate analysis and serve for objective decision-making. The avoidance of agricultural risks is a task of the first order to safeguard food security and thus reducing the vegetative periods in crops is an effective strategy to achieve it. The work is carried out in the Babahoyo canton, Los Ríos province on obtaining behavior models of air temperatures that facilitate, through the application of Differential Calculation, obtaining the dates of maximum temperatures, which would allow obtaining the periods of higher temperatures. thermal supply to accelerate growth and development processes. The dates of maximum temperature were located around decade 7, between March 13 and 17, results of the sum of probabilities for 75%. The sums of temperatures obtained fluctuate in the range 2170 – 2266 Celsius Degrees that guarantee the acceleration of the vegetative period, since they have 100% of the sum of probabilities of being reached. Observe a management directed to the selection of the period of highest temperature will reduce the risks of pests and extreme events, in addition to reducing inputs in agricultural production, which will increase the sustainability of the system.